Financial Spillovers to Emerging Markets During the Global Financial Crisis - Frank, Nathaniel (IMF Working Papers; Working Paper ;, 2009)
In this paper potential financial linkages between liquidity and bank solvency measures in advanced economies and emerging market (EM) bond and stock markets are analyzedduring the latest crisis. A multivariate GARCH model is estimated in order to gauge the extent of co-movements of these financial variables across markets. The findings indicate that the notion of possible de-coupling (in the financial markets) had been misplaced. While EM stock markets reached their peak in the last quarter of 2007, interlinkages between funding stress and equity markets in advanced economies and EM financial indicators were highly correlated and have seen sharp increases during specific crisis moments.